2017
DOI: 10.1017/ice.2017.13
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Bed Bug (Cimex lectularius) Introductions Into an Academic Medical Center

Abstract: reduction-program.html. Published 2014. Accessed July 10, 2016. 4. Dicks KV, Baker AW, Durkin MJ, et al. The potential impact of excluding funguria from the surveillance definition of catheter-associated urinary tract infection. Infect Control Hosp Epidemiol 2015;36:467-469. 5. Urinary tract infection (catheter-associated urinary tract infection [CAUTI] and non-catheter-associated urinary tract infection [UTI]) and other urinary system infection [USI]) events. Centers for Disease Control and Prevention website. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…One hospital reported finding bed bugs as frequently as every 2.2 days and, in the emergency department (ED), approximately every 4-5 days, resulting in significant institutional expense [2][3][4][5]. Survey and epidemiological studies suggest that many more patients with residential bed bug infestations are being seen by healthcare providers than the actual number of insects being identified by the healthcare providers [2,3,[6][7][8]. The estimated number of ED visits related to bed bugs increased seven-fold between 2007 and 2010 [9].…”
Section: Introductionmentioning
confidence: 99%
“…One hospital reported finding bed bugs as frequently as every 2.2 days and, in the emergency department (ED), approximately every 4-5 days, resulting in significant institutional expense [2][3][4][5]. Survey and epidemiological studies suggest that many more patients with residential bed bug infestations are being seen by healthcare providers than the actual number of insects being identified by the healthcare providers [2,3,[6][7][8]. The estimated number of ED visits related to bed bugs increased seven-fold between 2007 and 2010 [9].…”
Section: Introductionmentioning
confidence: 99%
“…The study population involved EMS agencies in and around Cleveland, Ohio, which is one of the most bed bug-infested cities in the United States [20]. At UH Cleveland Medical Center (UHCMC), a bed bug is found in the facilities on average every 2.2 days and every three to six days in the ED; however, the true number is likely underreported [6,[21][22][23]. A survey of UHCMC ED patients found that about one in 50 reported an active home bed bug infestation; 37% (253/680) reported a past history of being fed on by a bed bug, and 59% (415/702) reported knowing someone other than persons living in their home having a bed bug infestation in the past five years [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…The survey took place in Cleveland, OH, one of the most bed bug infested areas in the United States, and it shows that bed bug infestations are a significant problem for many of our ED patients [10]. The hospital in which the survey was performed previously reported finding a bed bug in the institution approximately every 2 days, with most insects found in the ED at a frequency of every 3-5 days [2, 5]. The direct annual costs for the ED to decontaminate a patient room due to a bed bug were approximately $50,000 per year [5].…”
Section: Discussionmentioning
confidence: 99%
“…Very little is known about the epidemiology of bed bugs in the emergency department (ED). For instance, the number of bed bug introductions in the ED is unknown and likely underreported partly because healthcare workers predominantly only find the larger insects, and no International Statistical Classification of Diseases and Related Health Problems (ICD-10) code exists for bed bug infested patients to study the problem [1, 2]. It is unclear if older and sicker ED patients are more likely to have a home bed bug infestation as well as the degree to which the insect can contribute to excess morbidity [3].…”
Section: Introductionmentioning
confidence: 99%